Comparing a GPS time link calibration with an optical fibre self-calibration with 200 ps accuracy. (30th March 2015) - Jiang, Z; Czubla, A; Nawrocki, J; Lewandowski, W; Arias, E F
Abstract: In Poland, an accurate two-way optical fibre time transfer (TWOTT) baseline of 420 km has been developed with a standard uncertainty of 112 ps. Meanwhile, the BIPM has been engaged in a pilot project to reduce the uncertainty of UTC GNSS time transfer calibrations from 5 ns to approximately 1.5 ns, for which it has developed a standard calibration scheme, named METODE, associated with an integrated portable GNSS calibration station. The TWOTT and the METODE respectively represent the world' s most advanced time transfer method and calibration facility. In July 2013, the BIPM calibrator and the TWOTT self-calibrated optical fibre transceivers were set up side by side to compare their results. This is the first time that an operational TWOTT has been used in accurate time transfer and the first time that a GNSS calibration method has been validated with a technique accurate to 200 ps. As the two systems are completely independent and the latter is one order of magnitude more accurate than the first, this comparison allowed validation of the METODE and its uncertainty. It also confirmed that any bias in the TWOTT is at most 1 ns.